2019
DOI: 10.1016/j.compchemeng.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Kaibel column: Modeling, optimization, and conceptual design of multi-product dividing wall columns

Abstract: In this work, we present the modeling, optimization, and conceptual design of a dividing wall column for the separation of four products, commonly referred to in the literature as a Kaibel column. For its solution, we propose and validate a rigorous tray-by-tray model, followed by its reformulation to include a mixed-integer nonlinear programming and a general disjunctive programming formulation to respond to the conceptual design problem attached to these complex configurations. Considering the validated mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…While the case study shown here is relatively simple, the IDAES-CMF has been applied to simulating and optimizing complex chemical and energy related processes, such as the removal of CO 2 from power plant flue gas. [38] The IDAES-CMF has also been applied to a range of other problem types, such as conceptual design and process intensification [39] and dynamic real-time optimization and control, [40] and non-linear robust optimization. [41] F I G U R E 1 8 Distribution of capital and operating cost with respect to the uncertainty considered in the kinetic parameters…”
Section: Step 11: Optimization Under Uncertaintymentioning
confidence: 99%
“…While the case study shown here is relatively simple, the IDAES-CMF has been applied to simulating and optimizing complex chemical and energy related processes, such as the removal of CO 2 from power plant flue gas. [38] The IDAES-CMF has also been applied to a range of other problem types, such as conceptual design and process intensification [39] and dynamic real-time optimization and control, [40] and non-linear robust optimization. [41] F I G U R E 1 8 Distribution of capital and operating cost with respect to the uncertainty considered in the kinetic parameters…”
Section: Step 11: Optimization Under Uncertaintymentioning
confidence: 99%
“…Luyben demonstrated that the energy consumption of distillation columns can increase, instead of decrease, when more stages are used due to the pressure drop increase by the addition of stage(s). Second, in the thermally coupled distillation configurations, like those in dividing wall columns (DWCs) or side rectifier columns, which are appearing economically attractive and have drawn much attention recently, vapor split must take place, and the distribution of the split vapor flows up into the two corresponding column sections is a direct result of the balance between the pressure drops of the two column sections …”
Section: Introductionmentioning
confidence: 99%
“…To handle disturbance and implementation error of DWCs, Luo et al [22] developed an online optimization method assisted with steady-state analysis. In addition, a sequential quadratic method using the mixed integer linear programming problem [23] or MINLP [24] approach was also used for conceptual design of DWCs. However, this kind of method is difficult to implement.…”
mentioning
confidence: 99%